Ultrasound Detection of Portomesenteric Venous Gas Is an Early Sign of Bowel Ischaemia in Non-Traumatic Abdominal Pain: Old Dogs, New Tricks—Four Cases Report. (23rd August 2022) - Di Capua, Mirko; Tonani, Michela; Paglia, Stefano
Abstract : Acute bowel ischemia is a severe disease often with a poor outcome. Early diagnosis can improve outcome, but atypical clinical manifestations and nonspecific laboratory and instrumental diagnostic findings may delay computed tomographic angiography (CTA). Portomesenteric venous gas (PVG), indirect sign of pneumatosis intestinalis, is considered a late finding with poor prognosis. We report four cases where PVG, easily identified through point-of-care ultrasonography (POCUS), was an early sign of bowel ischemia leading to a precocious diagnosis confirmed at CTA. In acute non-traumatic abdominal pain, an evidence of PVG could be an early ultrasonographic finding of bowel ischemia in the emergency department.